ANALISIS MELODI BEGAMALSUKU DAYAK KANCING KECAMATAN MELIAU KABUPATEN SANGGAU - Bumadius, Bumadius; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractData were analyzed qualitatively, with YohanesAben as interviewer and some people who active and know about traditional music, especially Begamal melody of Dayak KancingMeliau sub-district Sanggau district. Based on the analysis of data, it can be concluded that Begamal melody is the result of literal repetition from one melody pattern, whether it’s a vocal melody or kromong melody. Vocal melody of begamal using pentatonic scale which the sing process use ornament, but in Kromong melody used tetratonic scale. Begamal can be sung by man and woman. BasicallyBegamal music is played as a ritual music and be accompany music of traditional dance from Dayak Kancing tribe. Along with the times, Begamal music began to appear at art show in the context of entertainment. This research is expected to be able for being a stimulus of proclivity growth to learn Begamal music, especially melody of Begamal Dayak Kancing tribe Meliau sub-district Sanggau district.Keywords: Analysis, Begamal, Dayak Kancing, Meliau, Melody, Sanggau